A view of the Brazil-Malvinas confluence, March 2015. (June 2021) - Orúe-Echevarría, Dorleta; Pelegrí, Josep L.; Alonso-González, Iván J.; Benítez-Barrios, Verónica M.; Emelianov, Mikhail; García-Olivares, Antonio; Gasser i Rubinat, Marc; De La Fuente, Patricia; Herrero, Carmen; Isern-Fontanet, Jordi; Masdeu-Navarro, Marta; Peña-Izquierdo, Jesús; et al.
Abstract: The encountering of the subtropical Brazil Current (BC) and the subantarctic Malvinas Current (MC) along the western margin of the Argentine Basin forms the Brazil-Malvinas Confluence (BMC), one of the most intense open-ocean fronts in the world ocean and a site for the formation of intermediate water masses. Here, we provide a comprehensive description of the BMC based on physical and biogeochemical data – hydrographic stations, profiling floats and subsurface drifters – gathered in March 2015. We use these data in order to characterize the impinging and outflowing currents and to describe the cross- and along-frontal thermohaline structure. In addition, we compare the in-situ measurements with both climatological data and the Mercator Ocean eddy-resolving reanalysis. The hydrographic sections illustrate the contrasting properties between the two western boundary currents: warm, salty, nutrient- and oxygen-poor oligotrophic subtropical waters carried southward by the BC and the cold, fresh, oxygen- and nutrient-rich subantarctic waters carried northward by the MC. The frontal system is also characterized by the presence of thermohaline intrusions, with the cross-frontal gradients and along-front velocities sharpening as the colliding currents shape the frontal system. We also observe brackish waters spreading on top of the frontal jet as a result of both the confluence dynamics and off-shelf advection favored by north-easterly winds. These low-salinity waters are positively correlated with surface ageostrophic speeds over the frontal jet. The cruise data illustrates the high regional and mesoscale variability as compared with climatological conditions, and further document the submesoscale subsurface complexity, which is not properly captured by available operational models. Highlights: We describe the cross-and along-front thermohaline structure of the Brazil-Malvinas Confluence in March 2015. The eddy-resolving reanalysis reproduces the mesoscale variability but not the complex subsurface submesoscale structure. Brackish waters spread over the Confluence due to both confluence jet dynamics and off-shelf advection forced by the wind.